(untitled) (Orfeu, 2023)
This article aims to highlight the differences between music education and music therapy for people with disorders and disabilities. A descriptive bibliographic review was used as a methodology and the main authors of both areas studied were consulted to better clarify the contexts, applicability, approaches and professional training of each of the areas. The results point to different purposes between music education and music therapy: while music therapy focuses on health, music education focuses on teaching-learning.